Strategic management dynamics in cooperative development in Tanzania: Theory and practice - Kikula Jaraji S.; Msabila Dominik T. (Mzumbe University, 2025)
This book provides a fundamental, yet comprehensive coverage of strategic management in cooperatives since their inception in Tanzania. It provides the general overview of cooperative unions in terms of their genesis at a global level and then explains their introduction in Tanzania as well as the purpose of their introduction. The book provides not only the theoretical underpinnings and principles of strategic management in cooperative unions, but also unleashes and marshals some practical experiences from selected cases where the research was carried out. The book is destined to serve the instructional needs of business, education, public administration, and political science students in higher education institutions. It can also be used in alltypes of organisations including the government and nongovernment entities. The book is divided into seven chapters as follows: Chapter one covers the history of cooperative movement, chapter two deals with the concept of strategic management, chapter three covers strategic management and cooperative development, and chapter four deals with decision making. Also, chapter five deals with decision making techniques while chapter six covers creativity in decision making. Lastly, chapter seven deals with planning for cooperative development. The book is written in a reader-friendly simple language to enhance profound understanding of various concepts and techniques in strategic management. Students, lecturers and other stakeholders will find it a very useful resource in answering their different questions related to strategic management in cooperative unions in Tanzania. They will know various challenges that have been militating against the effective performance of cooperatives and even think of the best ways to address the identified challenges. Authors wish to express their sincere appreciation to all authors of all references that were consulted during the preparation of this book. Likewise, the respondents in Morogoro, Songea and Mbeya who were consulted during the study are highly acknowledged for they played not only a monumental but an instrumental role in the production of this book. We remain in high tune determined to enhance and expand the landmark frontiers of knowledge among as many readers as possible as we strongly believe that we are in the knowledge era where knowledge sharing stands to be not only important but vital in unravelling various developmental challenges we encounter in our contiguous milieux/vicinities